DETERMINAN KEPUTUSAN PEMBELIAN SECARA ONLINE PENGGUNA APLIKASI SHOPEE - Zulkifli Zulkifli; Muhammad Nur; Herizal Herizal (JURNAL LENTERA BISNIS, 2024)
The phenomenon of online shopping at this time which continues to grow, it’s not surprising that business people need to pay attention to the importance of consumer reviews and also provide the best quality of electronic services so that customers can purchase products in the marketplace. This research aims to analyze the factors influencing consumer purchase decisions of Shopee aplication users. These factors include Islamic advertising etnics, consumer psychology and social environment. This research applies quantitative techniques and it is analyzed using IBM SPSS version 22. The sampling method used purposive sampling and the number of samples used in this study amounted to 110 respondents source was distribution of questionnaires to Shopee users in East Lombok by online via WhatsApp. Analysis was carried out by several tests such as validity test, realibility test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the Islamic advertising etnics (X1) dan Consumer Psychology (X2) have a positive and significant effect on online purchasing decisions, while the social environment (X3) does not have affect on online purchasing decisions at Shopee (Y). The findings of this study can be reference uses as a reference for future researchers who will study similar problems. This research can also be a reference for companies to always be able to maintain aspects of Islamic advertising ethnics and consumer psychology in designing and determining effective and efficient markering policies. Key words: Purchase Decisions, Islamic Advertising Ethnics, Consumer Psychology, Social Environment